TABLE TENNIS TRAINING FACILITIES (British Journal of Global Ecology and Sustainable Development, 2024)
This article, which is presented, talks about the effectiveness of using various methods that are considered necessary when conducting table tennis training. Information is also provided on the necessary principles of physical education and sports training.